Внутрішня функціональна структура екологічної мережі Волинського Полісся (у межах Волинської області) - Карпюк, Зоя Костянтинівна; Karpiuk, Zoia K. (My University, 2014)
У роботі здійснено еколого-географічний аналіз структури і функціональної організації екологічної мережі регіону, встановлено закономірності їх територіального розподілу і просторово-часової динаміки, обґрунтовано заходи щодо оптимальної геопросторової організації. Проаналізовано природні умови формування складових частин екомережі та чинники антропогенного впливу, здійснено комп’ютерну обробку отриманих аналітичних даних та побудовано картографічну модель екологічного стану довкілля регіону. Проведено польові експедиційні дослідження та виявлено реальні шляхи міграційних біотичних переміщень, досліджено найтиповіші ландшафтні структури: місцевості, урочища й підурочища, якими ці переміщення відбуваються, оцінено просторову картину взаємного розміщення складових елементів регіональної екологічної мережі щодо цих міграційних ліній зв’язку, побудовано відповідні картосхеми. Здійснено оцінку структури земельного фонду регіону з метою виявлення перспективних площ для розширення природоохоронних територій та їх просторового об’єднання через систему біокоридорів. На базі вивчення сучасного стану функціональних елементів регіональної екологічної мережі та реальних міграційних потоків запропоновано необхідні заходи щодо удосконалення її територіальної організації через включення у структуру регіональної екомережі для забезпечення генетичного зв’язку функціональних елементів локального рівня.

In the thesis the ecological and geographical analysis of the structure and function of the ecological network in the region was carried out, regularities of the spatial distribution and the spatial – temporal dynamics were established, geospatial measures for optimal organization were grounded. The natural conditions of the components of the ecological network and anthropogenic factors influencing them were analyzed, computer analysis of the received analytical data was carried out and cartographic model of ecological state of the environment of the region was constructed. Importance of regional ecological network for the protection, conservation and restoration of the landscape and biological diversity of the region and its ecological balance was proved. A number of field researches were carried out and practical ways of biotic migration movements were discovered, the most common landscape structure was studied: areas, natural boundaries and sub boundaries on which migration movements occur, spatial pattern of the relative position of the spatial components of the regional ecological networks in accordance with these migratory lines was evaluated, corresponding maps were composed. The dynamics of the formation of territories and objects of nature reserves and the allocation of basic functional structural parts of the regional ecological network were analyzed. The most valuable natural protected areas that serve as potential cross-border elements in the formation of all-European ecological network were defined. The estimation of land reserves structure in the region with the aim to identify promising areas for expansion of protected areas and their spatial unification via biological corridors was carried out. Based on the study of the current state of the functional elements of the regional ecological networks and actual migration flows the appropriate measures for the improvement of the territorial organization of the structure due to the inclusion of regional ecological network for the genetic relationship between the functional elements of the local level was proposed.
Internal Functional Structure of Ecological Network of the Volyn' Polissia (in the Volyn' Region)
Робота виконана на кафедрі географії географічного факультету Східноєвропейського національного університету імені Лесі Українки Міністерства освіти і науки України
Keywords: регіональна екологічна мережа; міграційне переміщення; структурно-функціональний елемент; ландшафтне і біотичне різноманіття; екологічне ядро; екологічний коридор; буферна зона; regional ecological network; structural and functional element; landscape and biotic diversity; ecological core; ecological corridors; buffer zone; migratory movements